A prospective study on glucagon responses to oral glucose and mixed meal and 7‐year change in fasting glucose. (12th April 2019) - Koopman, Anitra D. M.; Beulens, Joline W.; van der Heijden, Amber; Elders, Petra; Dekker, Jacqueline M.; Alssema, Marjan; Rutters, Femke
Summary: Introduction: The role of insufficient glucagon suppression after an oral load in the development of type 2 diabetes mellitus is unclear. The aim of this study was to examine the association between glucagon responses at baseline and fasting glucose levels 7 years later. Methods: Data of the Hoorn Meal Study were used, an observational cohort study among 121 persons without diabetes with a mean age of 61.1 ± 6.7 years and 50% being female. The glucagon response to an oral glucose tolerance test and mixed meal test was expressed as early and late incremental area under the curve. The association with change in fasting glucose levels at follow‐up was assessed by linear regression analysis. Results: The early glucagon response following the mixed meal test was associated with an increase in fasting glucose levels of 0.18 mmol/L (95%‐CI: 0.04‐0.31, P  = 0.01), per unit increase in the incremental area under the curve of glucagon, adjusted for confounders. No significant associations were observed for the late response after the mixed meal test or oral glucose tolerance test. Conclusions: Within a population without diabetes, relative lack of glucagon suppression early after a meal was associated with increased glucose levels over time, suggesting a role of insufficient glucagon suppression in the deterioration of glycaemic control.